Some symmetry properties of gyre flows. (October 2022) - Constantin, Olivia; Kalaj, David
Abstract: The large gyre systems of near-surface almost-circular ocean currents formed by global wind patterns and the effect of the Earth's rotation often present symmetry properties. By means of maximum principles, we infer certain symmetry properties from the specific structure of such flows. Our approach uses the stereographic projection, which allows us to turn the governing equations for steady flows on a rotating sphere into semilinear elliptic equations in the plane. Furthermore, we discuss the possibility of using conformal mappings to study specific flows.